TRANSLATION ANALYSIS OF LITURGICAL SPECIALIZED VOCABULARY IN YESUS ANAK MANUSIA - Reinaldo Suryo Negoro (Haluan Sastra Budaya, 2019)
This article discusses the translation of liturgical specialized vocabulary (LSV) found in Yesus Anak Manusia novel. This article aims to identify the translation techniques used by the translator in translating LSV. The data were collected by using content analysis and focus group discussion. Afterward, the data were analyzed using Spradley’s analysis model. The result of this analysis shows that there are 13 techniques used by the translator in translating LSV in Jesus Son of Man novel as the source text of Yesus Anak Manusia novel. 11 translation techniques affect the translation to be an accurate translation, 3 translation techniques generate less accurate translation and 2 translation techniques generate inaccurate translation. 10 translation techniques generate acceptable translation, 6 translation techniques generate less acceptable translation, and a translation technique generates unacceptable translation.